Live-Stream Shopping: Impact of Social Attraction, Social Presence, Parasocial Interaction, and Positive Emotion on Purchase Intention - Wensi Febtiana; Afrima Widanti (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: The increasing popularity of live-stream shopping underscores its growing significance in the e-commerce landscape. However, research on the formation of purchase intention within this context remains limited. This study investigates the influence of social attractiveness and social presence on purchase intention, with parasocial interaction as a mediating variable and positive emotions as a moderating variable among Shopee Live users.Method: This study adopts a quantitative research approach, employing purposive sampling targetting Shopee Live users in Indonesia. Data were collected through an online questionnaire administered via Google Forms and disseminated through social media platforms, including Facebook, Instagram, Telegram, and WhatsApp. A total of 324 valid responses were analyzed using Structural Equation Modeling (SEM) with AMOS 23.Result: The findings indicate that social attraction does not exert a significant influence on either parasocial interaction or purchase intention. Conversely, social presence positively affects both parasocial interaction and purchase intention. Furthermore, parasocial interaction positively influences purchase intention but does not mediate the relationship between social attractiveness and purchase intention. Instead, it functions as a positive mediator between social presence and purchase intention. Additionally, positive emotions do not moderate the relationship between parasocial interaction and purchase intention.Practical Implications for Economic Growth and Development: The findings suggest that e-commerce platforms should enhance social presence and parasocial interactions in live-stream shopping to stimulate purchase intention, drive digital transactions, strengthen business competitiveness, foster consumer spending, and support the sustainable growth of the digital economy.